Who runs the place? : the evolving role of corporate centre in the strategy-making process : an empirical investigation of a major Russian multi-business corporation - Laptev, Andrey (Cranfield University, 2011)
This research was inspired by a particular business problem – the search for an optimal model of strategy-making process in Severstal, a major Russian metals and mining company going through a period of rapid growth and transformation. The research reports on the results of a longitudinal explorative case study based on two distinct empirical projects. The first project addressed strategy process nature, participants, roles of corporate centre, time perspective and impact of the external environment. Its results highlighted the importance of CEO leadership and personal traits, which became the principal focus of the second empirical project. The key empirical contribution of the research was definition of "leader-focused decentralisation" as a particular approach to strategy-making in a multi-business group. This approach combines decentralized, bottom-up, business units-led generation of strategic proposals and initiatives with a crucial role of a company leader as a deeply involved decision-maker, presiding over a small and lean corporate centre with minimal corporate rules and bureaucracy. In Severstal’s case, the "leader-focused decentralisation" approach to strategy was a good match to its volatile yet rewarding external environment. The suggested model can be seen as an empirically-derived step towards a theoretical synthesis of "activist" vs. "detached" views of corporate centre roles in relation to strategy process in multi-business firms. It exhibited some distinctive features which were not yet described in other contexts, including co-existence of strong entrepreneurial leadership and organisational decentralisation. From a practical standpoint, the research highlighted weaknesses and limitations of existing strategy-making model and offered a background for the discussion of ways to develop it in the future.
Keywords: Strategy Process; Corporate Centre; Leadership; Configurations; Decentralisation; Multi-Business Group; Russia